SACRED, CORRUPT, AND HEROIC: TYPOLOGIES OF THE USTAZ IN INDONESIAN HORROR FILM - Namira Choirani Fajri
In the post–New Order era, the horror-religious genre in Indonesia has experienced a surge in popularity, reflecting a complex interplay of public anxieties and fantasies regarding religious authority. Although this phenomenon has attracted scholarly attention, existing interpretations remain largely confined to a “desacralization” framework that narrows the understanding of the diversity of ustaz figures. Such approaches often overlook the connection between on-screen representations and broader socio-cultural dynamics, particularly the shifting locus of religious authority within the new media ecosystem. This study adopts a literary and cultural studies perspective, employing a functional typology analysis of selected Indonesian horror-religious films released after New Order era. The analysis identifies three main archetypes of the ustaz: sacred yet vulnerable, reflecting uncertainty over the relevance of traditional authority; corrupt or corporatized, offering a critique of the commodification of preaching; and heroic and re-sacralized, presenting a collective fantasy of an ideal Islamic leader who is modern, strong, and protective. The findings reveal that these archetypes represent a symbolic arena where the public negotiates the crisis and reconstruction of religious authority in the post–New Order era. Horror-religious cinema does not merely mirror reality but actively intervenes in it: packaging societal anxieties, critiques, and aspirations into accessible yet meaning-laden visual narratives. This research thus positions film as a strategic interdisciplinary pathway for understanding the intersections of religion, media, and the market in Indonesia, while offering a significant contribution to global discourses on the contestation of religious authority.